A whole system approach to promoting health and human performance in military settings as vital prerequisites for force readiness and operational capability - Fallowfield, Joanne L.; Drain, Jace R.; Carins, Julia; Kilding, Helen; Williams, Emma; Fisher, Ben; Hayhurst, Debra; Gourlay, Alysia; Olivotto, Simon; Bullock, Garrett (Frontiers in Physiology, 2025)
The military role and associated occupation-specific training contribute to a high musculoskeletal injury (MSKI) incidence and poor health burden. A fit Force is better prepared for achieving mission success, as well as being more resilient to operational physical and cognitive demands. Conversely, MSKI and ill-health reduce Force readiness. Internationally, militaries have common workforce capacity and capability challenges, where more is being asked of fewer personnel. Unhealthy body composition, low aerobic fitness, poor movement control and poor health behaviours interact to adversely impact human performance. The military workplace—including leadership prioritisation and resource allocation—has generally not strategically managed and supported health and performance interventions to maximise people outcomes. Efforts have focused on the individual and their capabilities to address their ill-health or poor performance. Only through system-based thinking—adopting a Whole System Approach (WSA)—can effective evidence-based interventions to promote health and human performance be: holistically developed; successfully implemented at scale across geographically dispersed organisations to realise meaningful and enduring outcomes; and impacts measured and evaluated. This paper provides a synthesis of scientific and practice-based evidence to operationalise system-thinking in developing integrated WSA workplace interventions for military health and human performance, and measure effect and return on investment. Whilst militaries are recognising the need for a paradigm shift to realise the benefits of effective health and performance interventions, persuasive financial arguments could assist with overcoming large-organisation inertia. Moreover, system-based thinking—addressing individual and organisational factors—could maximise military health and performance, foster resilience and deliver operational effectiveness.